2016
DOI: 10.1007/s00427-016-0534-7
|View full text |Cite
|
Sign up to set email alerts
|

The sex-limited effects of mutations in the EGFR and TGF-β signaling pathways on shape and size sexual dimorphism and allometry in the Drosophila wing

Abstract: Much of the morphological diversity in nature–including among sexes within a species–is a direct consequence of variation in size and shape. However, disentangling variation in sexual dimorphism for both shape (SShD), size (SSD) and their relationship with one another remains complex. Understanding how genetic variation influences both size and shape together, and how this in turn influences SSD and SShD is challenging. In this study we utilize Drosophila wing size and shape as a model system to investigate ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…4 B and C). This is also consistent with a recent report that fly wings display sex-dependent effects in different genetic backgrounds (43). Additionally, multiple studies have suggested a role of sex on the severity of defects in individuals with RASopathies.…”
Section: Resultssupporting
confidence: 92%
“…4 B and C). This is also consistent with a recent report that fly wings display sex-dependent effects in different genetic backgrounds (43). Additionally, multiple studies have suggested a role of sex on the severity of defects in individuals with RASopathies.…”
Section: Resultssupporting
confidence: 92%
“…While these findings implicated multiple genes within each CNV region towards conserved cellular processes in neuronal tissues, the conserved role of these genes in non-neuronal tissues is not well understood. The Drosophila wing is an effective model system to evaluate such developmental defects, as key components of conserved signaling pathways, such as Notch, epidermal growth factor receptor (EGFR), Hegdehog, and Wnt pathways, were identified using fly wing models [32][33][34][35][36][37][38]. Although fly wing phenotypes cannot be directly translated to human phenotypes, defects observed in fly wings can be used to assess how homologs of human disease genes alter conserved cellular and developmental mechanisms.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Implementing these approaches demonstrates size and shape differences between male and female populations of Drosophila via systematic analysis of features extracted. In particular, females had significantly larger wings (p-value < 0.001) consistent with sexual dimorphism of insulin signaling activity (Testa and Dworkin 2016) while males had significantly larger trichome densities (p-value < 0.001). We also show how variable regulation of growth is necessary for maintaining perfect scaling of anatomical axes such as the AP axis and PD axis of the wing.…”
Section: Mapper Provides Multiplexed Analysis Tools For High Dimensiomentioning
confidence: 68%
“…The high dimensional morphometric fingerprint generated by MAPPER separates the male and female population of wings (Figure 2E,G). The sex-based difference in patterning and size of adult Drosophila melanogaster wing is known and well studied (Testa and Dworkin 2016). We also show that the EFD-based features can be used to probe into this sex-related shape changes more locally (Figure 2H).…”
Section: Resultsmentioning
confidence: 99%